A Bibliometric Analysis of First 45 Years of Journal of Management. Issue 1 (3rd April 2022) - Ohlan, Ramphul; Singh, Rajbir; Kaur, Sharanjeet; Ohlan, Anshu
Abstract: The knowledge domain of business research has grown tremendously over the last five decades. This study investigates the leading trends in the intellectual structure of the Journal of Management ( JOM ) during the 1975–2019 timeframe. It analyses the most frequent authors, institutions, countries, citation performance, and emerging themes of JOM . In so doing, this article maps co-citation, co-authorship, and co-occurrence networks by employing VOSviewer software. The findings indicate that trends in the number of publications and several indicators of the impact of research published in JOM are encouraging. The results show a surge in the dispersal of the authors across the world, especially from the United Kingdom, Netherlands, Canada, and Australia. Likewise, multi-authored publications have witnessed robust growth. The burst detection analysis performed employing CiteSpace software indicates that the recent contribution of JOM is mainly in strengthening a new perspective in the field of well-being, motivation, abusive supervision, agency theory, and social network.